1988
DOI: 10.1007/bf00636615
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of the haemodynamic effects of anabolic steroids in rats

Abstract: The haemodynamic effects of 6 weeks nandrolone decanoate treatment (total dose 30 mg.kg-1) (SG I, n = 12) and their reversibility were studied in anaesthetised, open-chest male rats exposed to 5 min isoproterenol (2.5 micrograms.kg-1) and CaCl2 (25.0 mg.kg-1) loads. In SG I, the heart weight and its ratio to body weight were greater than in the untreated rats (CG I, n = 13) (p less than 0.05 and p less than 0.01 respectively). The initial heart rate and the inotropic and chronotropic responses to isoproterenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
0
15
0
2
Order By: Relevance
“…CS NE CE NS in sedentary and exercised rats (14,15). We demonstrated that exercised animals exhibited a greater (two-way ANOVA, P < 0.05) accumulation of HSP72 in the cardiac muscle compared to sedentary animals (mean ± SEM; 677.16 ± 129.14 vs 246.24 ± 46.30 relative unit, respectively), independently of the nandrolone administration.…”
Section: Hsp73 Hsp72mentioning
confidence: 66%
“…CS NE CE NS in sedentary and exercised rats (14,15). We demonstrated that exercised animals exhibited a greater (two-way ANOVA, P < 0.05) accumulation of HSP72 in the cardiac muscle compared to sedentary animals (mean ± SEM; 677.16 ± 129.14 vs 246.24 ± 46.30 relative unit, respectively), independently of the nandrolone administration.…”
Section: Hsp73 Hsp72mentioning
confidence: 66%
“…In the studies where baseline mechanical function of the hearts was compromised, the doses of different AAS were somewhat higher [27,50]. In particular, while…”
Section: Discussionmentioning
confidence: 99%
“…In in vivo experiments ND treatment altered the inotropic and chronotropic left ventricular response as well as the vascular responses to isoproterenol [9]. These apparent contrasting findings ( [7] versus [8,9]) can find a reason on the intricate interplay existing among pre-load, post-load, heart geometry and chronotropic effects over inotropic response of the heart [10]. Moreover, the ventricular stiffness and, thus, the response to stretch of hypertrophic hearts is altered [7].…”
Section: Introductionmentioning
confidence: 98%
“…However, the same chronic treatment produced hypertrophy and a decrease in myocardial contractile reserve to ␤-adrenoceptor stimulation [8]. In in vivo experiments ND treatment altered the inotropic and chronotropic left ventricular response as well as the vascular responses to isoproterenol [9]. These apparent contrasting findings ( [7] versus [8,9]) can find a reason on the intricate interplay existing among pre-load, post-load, heart geometry and chronotropic effects over inotropic response of the heart [10].…”
Section: Introductionmentioning
confidence: 99%